Aktualisasi Makna Kerjasama (Living Al-Qur'an-Hadist di Desa Koto Petai-Kerinci-Jambi) - Rasidin Rasidin; Nurfadliyati Nurfadliyati; Kusmana Kusmana (Institut Agama Islam Negeri (IAIN) Curup, 2021)
Actualization of the Cooperation Meaning (Living Al-Qur'an-Hadith in Koto Petai Village-Kerinci-Jambi)The purpose of this study is to examines how the actualization of the meaning of cooperation in the Koto Petai community. Based on this research, some forms of cooperation in the Koto Petai community, such as: Bampok, recitation on Ramadan night, slaughtering cow on Eid al-Fitr, 'skuduopihak